2022
DOI: 10.1108/edi-04-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Résumé screening heuristic outcomes: an examination of hiring manager evaluation bias

Abstract: PurposeHiring managers commonly rely on system-justifying motives and attitudes during résumé screening. Given the prevalent use of modern résumé formats (e.g. LinkedIn) that include not only an applicant's credentials but also headshot photographs, visible sources of information such as an applicant's race are also revealed while a hiring manager simultaneously evaluates a candidate's suitability. As a result, such screening is likely to activate evaluation bias. The purpose of this paper is to examine the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…First, we were not able to use LinkedIn specifically, so our profiles may not have been perceived as legitimate as they would be in practice. While most hiring studies have used real LinkedIn profiles, a few created replicas (e.g., Campbell & Hahl, 2022; Moore et al, 2023; Paik et al, 2014). We simulated the format as closely as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we were not able to use LinkedIn specifically, so our profiles may not have been perceived as legitimate as they would be in practice. While most hiring studies have used real LinkedIn profiles, a few created replicas (e.g., Campbell & Hahl, 2022; Moore et al, 2023; Paik et al, 2014). We simulated the format as closely as possible.…”
Section: Discussionmentioning
confidence: 99%
“…To test our proposed research model, we used an experimental design where participants evaluated two LinkedIn‐like profiles for a position. This approach, where personnel decisions are simulated, and candidate demographic characteristics (like gender and race) are manipulated, is common both in hiring discrimination studies in general (Moore et al, 2023; Neumark, 2018) and those focused specifically on hiring bias on LinkedIn (e.g., Campbell & Hahl, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, efficient HR practices ensure that the organization is staffed with the right people positioned in the best-fitted roles, with the necessary skills and resources to meet its objectives. By aligning the HR strategies with the organization’s goals, an organization can ensure that its workforce is properly positioned, motivated and trained to perform at their best and contribute to the overall long-term success, regardless of the size of the organization (Moore et al , 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the recent years, the aim of adopting digital recruitment in companies has been discussed by various researchers (Ahmed, 2018; Patterson et al , 2016). This issue has particular importance because literature (Moore et al , 2023) showed that companies could increase hiring efficiency by integrating technology into the recruitment process and updating the recruitment procedures.…”
Section: Introductionmentioning
confidence: 99%